2021
DOI: 10.1097/sih.0000000000000600
|View full text |Cite
|
Sign up to set email alerts
|

Distance Learning During COVID-19 Mitigates Learning Loss for Interprofessional Education

Abstract: On-site interprofessional education (IPE) simulation is primarily used to teach students teamwork, communication, and crisis resource management. Participants view it as an educational environment in which to acquire and consolidate skills. Virtual IPE simulation is traditionally seen as an opportunity to supplement, complement, and reinforce on-site IPE (OI). We used VI as the sole simulation method during the COVID-19 pandemic to provide IPE because of constraints of social distancing. The VI resulted in sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Included studies represented 14 different countries. There was a North American predominance to authorship, with 30 studies featuring authors located in the United States 17–46 and 5 studies included authors from multiple countries 23,27,47–49 Figure 2. highlights the reported origins of all included studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Included studies represented 14 different countries. There was a North American predominance to authorship, with 30 studies featuring authors located in the United States 17–46 and 5 studies included authors from multiple countries 23,27,47–49 Figure 2. highlights the reported origins of all included studies.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, less than half of the included studies were found to have a low risk of bias (n = 27/54, 49%) as seen in Appendix B (Table, Supplemental Digital Content 2, http://links.lww.com/SIH/A983). Of the 16 studies that were evaluated with the NIH assessment tool (NHBLI, NIH) for prestudies and poststudies with no control group, 18,19,21,22,26,29,33,34,36,38,47,49,53–56 more than half were assessed to be at low risk for bias (n = 9/16, 56%) 21,26,29,33,34,36,38,47,54 . Twenty-eight studies additionally were evaluated using the appropriate CASP tools 17,20,23,25,27,30–32,35,37,39,40,43,44,46,48,50–52,55,57–64 .…”
Section: Resultsmentioning
confidence: 99%
“…Basically, students have been divided into two camps, those who prefer online (taking into account significant advantages that have been discussed previously) and those who prefer offline education (as they are still followers of the traditional way of education and expressed a number of cons they experienced during online studies). Mostly the choice of one or another educational mode depends on the self-organization of the learner (15,16). Students who want to obtain knowledge will do it no matter what circumstances they are put in by adjusting their time to practice online on virtual platforms or to prepare for important medical exams while having extra time staying at home.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 Researchers who have examined the impact of virtual IPE concluded that virtual experiences were successful in promoting interprofessional competencies among participating students. 28,[30][31][32] The virtual platform makes it possible to bring large numbers of students from multiple health professions and different geographical locations together in a collaborative space. Even as pandemic restrictions are lifted and in-person simulations and rotations have returned to curricula nationwide, the virtual platform provides a means of curating effective interprofessional (IP) experiences.…”
Section: Virtual Ipe Researchmentioning
confidence: 99%